Stroke caused auditory attention deficits in children - Karla Maria Ibraim da Freiria Elias; Maria Valeriana Leme de Moura-Ribeiro (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To verify the auditory selective attention in children with stroke. METHODS: Dichotic tests of binaural separation (non-verbal and consonant-vowel) and binaural integration - digits and Staggered Spondaic Words Test (SSW) - were applied in 13 children (7 boys), from 7 to 16 years, with unilateral stroke confirmed by neurological examination and neuroimaging. RESULTS: The attention performance showed significant differences in comparison to the control group in both kinds of tests. In the non-verbal test, identifications the ear opposite the lesion in the free recall stage was diminished and, in the following stages, a difficulty in directing attention was detected. In the consonant- vowel test, a modification in perceptual asymmetry and difficulty in focusing in the attended stages was found. In the digits and SSW tests, ipsilateral, contralateral and bilateral deficits were detected, depending on the characteristics of the lesions and demand of the task. CONCLUSION: Stroke caused auditory attention deficits when dealing with simultaneous sources of auditory information.